Preventive Role of Salsalate in Diabetes Is Associated With Reducing Intestinal Inflammation Through Improvement of Gut Dysbiosis in ZDF Rats - Zhang, Xinrong; Cui, Xiao; Jin, Xiaofang; Han, Fei; Wang, Jingyu; Yang, Xiaoyun; Xu, Jie; Shan, Chunyan; Gao, Zhongai; Li, Xiaochen; Zuo, Minxia; Yang, Juhong; et al. (Frontiers in Pharmacology, 2020)
Abstract A safe and effective approach is needed to prevent and reduce the incidence of diabetes worldwide. The hypoglycemic efficacy of salicylic acid (salsalate, SAL), which has anti-inflammatory properties, has been empirically demonstrated in studies conducted at the Joslin Diabetes Center and elsewhere. Here, we investigated the potential role of SAL in preventing the onset of diabetes in Zucker diabetic fatty (ZDF) rats and attempted to elucidate its underlying mechanisms. ZDF and Zucker lean (ZL) rats were administered a high-fat diet with or without SAL intervention and their relative rates of diabetes were compared. Our results showed that all rats in the placebo group developed diabetes, whereas only 10% of the SAL-treated rats presented with impaired glucose tolerance (IGT). None of the latter progressed to diabetes. Relative to the untreated rats, SAL lowered plasma glucagon and insulin while improving insulin sensitivity and β-cell function. SAL may protect against hyperglycemia by increasing the microbial diversity, ameliorating gut dysbiosis, restoring intestinal epithelial cell connections, inhibiting endotoxin influx into the blood, and attenuating inflammation. Together, these findings suggest that SAL may be a candidate prophylactic therapy against diabetes. The protective role of SAL may be attributed to its ability to reduce intestinal inflammation and improve gut dysbiosis.